Nevermore : The Final Maximum Ride Adventure - Patterson, James 1947- (New York : Little, Brown, 2012)
Max, Fang, and Dylan prepare for the ultimate confrontation as a mysterious group threatens to reduce the world's population by ninety-nine percent by killing all those who are not enhanced.
Keywords: Friendship -- Fiction; Magic -- Fiction; Genetic engineering -- Fiction; Adventure fiction